Wordwall Website as a Learning Media in Teaching English for Seventh Grade Students at SMPN 2 Tidore Kepulauan - Husen, Nursakina (Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to examine the effectiveness of Wordwall, a web-based game-based learning platform, in enhancing student engagement in English language learning for seventh-grade students at SMPN 2 Tidore Kepulauan. The study employed a Classroom Action Research (CAR) design consisting of two cycles, each comprising the stages of planning, implementation, observation, and reflection. Data were collected through observation, interviews, and questionnaires, and analyzed qualitatively and descriptively to assess students’ activeness, motivation, and participation. The findings indicate that prior to the intervention, classroom activities were predominantly teacher-centered, resulting in limited student involvement. Following the integration of Wordwall, student engagement improved significantly across all indicators. The percentage of students asking questions increased from 30% to 80%, answering questions from 20% to 90%, participating in discussions from 35% to 90%, and completing tasks from 50% to 100%. The overall average of student activeness rose from 30% in Cycle I to 90% in Cycle II. These results demonstrate that the use of Wordwall as an interactive instructional medium is effective in fostering student motivation, promoting active participation, and creating a more learner-centered and engaging English learning environment.